Cognitive Function and Health Literacy Decline in a Cohort of Aging English Adults - Kobayashi, Lindsay C.; Wardle, Jane; Wolf, Michael S.; von Wagner, Christian (Journal of general internal medicine : JGIM, 2015)
ABSTRACT BACKGROUND Low health literacy is common among aging patients and is a risk factor for morbidity and mortality. We aimed to describe health literacy decline during aging and to investigate the roles of cognitive function and decline in determining health literacy decline. METHODS Data were from 5,256 non-cognitively impaired adults aged ≥ 52 years in the English Longitudinal Study of Ageing. Health literacy was assessed using a four-item reading comprehension assessment of a fictitious medicine label, and cognitive function was assessed in a battery administered in-person at baseline (2004–2005) and at follow-up (2010–2011). RESULTS Overall, 19.6 % (1,032/5,256) of participants declined in health literacy score over the follow-up. Among adults aged ≥ 80 years at baseline, this proportion was 38.2 % (102/267), compared to 14.8 % (78/526) among adults aged 52–54 years (OR = 3.21; 95 % CI: 2.26–4.57). Other sociodemographic predictors of health literacy decline were: male sex (OR = 1.20; 95 % CI: 1.04–1.38), non-white ethnicity (OR = 2.42; 95 % CI: 1.51–3.89), low educational attainment (OR = 1.58; 95 % CI: 1.29–1.95 for no qualifications vs. degree education), and low occupational class (OR = 1.67; 95 % CI: 1.39–2.01 for routine vs. managerial occupations). Higher baseline cognitive function scores protected against health literacy decline, while cognitive decline (yes vs. no) predicted decline in health literacy score (OR = 1.59; 95 % CI: 1.35–1.87 for memory decline and OR = 1.56; 95 % CI: 1.32–1.85 for executive function decline). CONCLUSIONS Health literacy decline appeared to increase with age, and was associated with even subtle cognitive decline in older non-impaired adults. Striking social inequalities were evident, whereby men and those from minority and deprived backgrounds were particularly vulnerable to literacy decline. Health practitioners must be able to recognize limited health literacy to ensure that clinical demands match the literacy skills of diverse patients.